Pembentukan Lingkungan Bahasa Arab di MA Dafi Pesantren Al Qur’an Science Sidoarjo - Yazid, Ghibran Atsqolani; Imam Fauji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the strategies for developing an Arabic language environment at MA Dafi Pesantren Al Qur’an Science and its impact on students' language skills. The research employs a qualitative case study approach through observation, interviews, and documentation. The findings indicate that the formation of the Arabic language environment is implemented systematically through various programs such as muhadatsah (daily conversation), insya’ (essay writing), imla’ (dictation), and Yaumul Lughah (Language Day). Both the physical and social environments are designed to support the daily use of Arabic by the students. This strategy not only enhances students’ speaking (maharah kalam) and writing (maharah kitabah) skills but also fosters a consistent and enjoyable language culture. The positive impact of the program includes increased student confidence, improved writing skills, and the institution’s growing reputation as a leading center for Arabic language education. MA Dafi has also become a reference model for other educational institutions and produces alumni with high competence and competitiveness in both academic and professional fields, domestically and internationally.